Is "proof" the Eighth "P" of Service? A Conceptual Model and Propositions. Issue 4 (2nd October 2017) - Moorthi, Y. L. R.; Roy, Subhadip
ABSTRACT: The article aims at making a conceptual contribution to services marketing literature by proposing an eighth "P" called "proof." Proof is a simple operational measure or an intuitive indicator that helps the customer quickly assess the efficacy of a service. The article discusses services marketing literature and develops propositions that underscore the importance of proof as the eighth P. When proof is provided about a service to the customer, it affects all service outcomes (i.e., service evaluation, purchase intent, customer satisfaction, and repurchase intent). Though conceptual, the article provides practical implications as well.